Current status of ethnobotany research on palms from Peru - Joaquina Albán; Betty Millán; Francis Kahn (Revista Peruana de Biología, 2014)
The current situation concerning research in ethnobotany and economic botany of Peruvian palms is analyzed through a review of the literature with emphasis on knowledge related to uses and vernacular names. Of the 136 Peruvian palm species, 104 have at least one use. A total of 268 different uses distributed in 16 categories were registered. The most frequent categories are "construction", "edible", "craft industry" and "medicinal". There are 109 palm species with at least one vernacular name in Peru. The consulted literature is analyzed in four categories: (i) general studies in economic botany, (ii) ethnographic and ethnobiological studies, (iii) studies of South-American palms of economic interest, (iv) studies that exclusively deal with the useful Peruvian palms. Ethnobotanical knowledge of Peruvian palms proves to be essentially descriptive, with much repetitive information. Studies that significantly contribute to the genetic or agronomical improvement of the economically promising palms are rare.